2016
DOI: 10.1002/adma.201601425
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Nanoscale Electric Field Control of Magnetism by Nanoionics

Abstract: Direct, nonvolatile, and reversible control of nanomagnetism in solid-state ferromagnetic thin films is achieved by controlling the chemical composition of the film through field-driven ion redistribution. The electric field-driven de-intercalation/intercalation of lithium ions can result in ≈100% modulation of the magnetization and drives domain wall motion over ≈100 nm. High-speed and multilevel magnetic information storage is further demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 51 publications
0
45
0
Order By: Relevance
“…[164,165] In this respect, Zhu et al [164] reported on ≈100% magnetization modulation of magnetic domains and reversible domain wall motion over a distance of ≈100 nm in SRO/LiFe 5 O 8 layers, by controlling the deintercalation/intercalation of Li + ions. [164,165] In this respect, Zhu et al [164] reported on ≈100% magnetization modulation of magnetic domains and reversible domain wall motion over a distance of ≈100 nm in SRO/LiFe 5 O 8 layers, by controlling the deintercalation/intercalation of Li + ions.…”
Section: Me Coupling Via Ionic Intercalationmentioning
confidence: 99%
“…[164,165] In this respect, Zhu et al [164] reported on ≈100% magnetization modulation of magnetic domains and reversible domain wall motion over a distance of ≈100 nm in SRO/LiFe 5 O 8 layers, by controlling the deintercalation/intercalation of Li + ions. [164,165] In this respect, Zhu et al [164] reported on ≈100% magnetization modulation of magnetic domains and reversible domain wall motion over a distance of ≈100 nm in SRO/LiFe 5 O 8 layers, by controlling the deintercalation/intercalation of Li + ions.…”
Section: Me Coupling Via Ionic Intercalationmentioning
confidence: 99%
“…Apart from this, a new promising class of Li‐based RS materials has recently been observed . Such a class, which embodies oxide‐based RS devices for memristive systems with Li‐based nanobatteries, is of substantial technological relevance to the state‐of‐the‐art.…”
Section: Introductionmentioning
confidence: 99%
“…Such a device can show tunnel magnetoresistance (TMR) effects with a high (low) resistance if the magnetization directions of the two ferromagnetic electrodes are parallel (antiparallel). [26] Magnetic domain wall motion, driven by the expansion of the magnetic domains, was further observed for distances over 100 nm. When the ZnO film is thin enough to serve as an electron tunneling layer, TMR effect can be observed from the electrically controlled formation of MTJs (Figure 13j).…”
Section: Magnetic Nanostructuresmentioning
confidence: 91%
“…Moreover, the filament was found to grow from the anode toward the cathode and was composed of discrete Pd nanoparticles, suggesting that the mobility and the redox rate of Pd 2+ ions in SiO x dielectric film are low. [26] Under a reversed bias voltage, the removed Li + ions move back into the switching material, which increases the Li content and restores the device to the HRS. These materials generally have cations forming weak ionic bonds with the immobile anions.…”
Section: Cation-driven Rs Effectsmentioning
confidence: 99%
See 1 more Smart Citation